2000
DOI: 10.3141/1706-01
|View full text |Cite
|
Sign up to set email alerts
|

Testing for the Significance of Induced Highway Travel Demand in Metropolitan Areas

Abstract: The theory o f induced growth in vehicle travel hypothesizes that highway improvements which add capacity to a specific corridor or regional transportation network will attract increased levels of vehicle traffic. This relationship of highway capacity to travel demand is an important consideration when evaluating how effective highway expansion alternatives will be in solving transportation problems. Two different but complementary empirical studies were conducted to quantify the effect of highway system impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 8 publications
(15 reference statements)
5
19
0
2
Order By: Relevance
“…In that some of this travel increase represents route diversions, the "induced demand" elasticity of newly produced VMT is likely even smaller. These results, which are more in line with those of several recent disaggregate, person-level studies of induced demand (Strathman, et al, 2000;Barr, 2000), suggest that past estimates of induced demand derived from lane-mile elasticities have overstated near-term impacts.…”
Section: Short-run Model Summarysupporting
confidence: 86%
“…In that some of this travel increase represents route diversions, the "induced demand" elasticity of newly produced VMT is likely even smaller. These results, which are more in line with those of several recent disaggregate, person-level studies of induced demand (Strathman, et al, 2000;Barr, 2000), suggest that past estimates of induced demand derived from lane-mile elasticities have overstated near-term impacts.…”
Section: Short-run Model Summarysupporting
confidence: 86%
“…Axhausen 6 2.0 Literature review Goodwin (1992Goodwin ( , 1996, Noland and Levinson (2000), Graham and Glaister (2004) and Goodwin et al (2004) provide overviews of known income, price and supply elasticities of car ownership and demand for transport services, measured in vehicle miles travelled. Similar analyses can be found in the works of Oum (1992), Cerwenka and Hauger (1996), Cairns et al (1998) de Corla-Souza andCohen (1999), Lee et al (1999), Barr (2000), Fulton et al (2000), Noland and Cowart (2000), Noland (2001) and Cervero and Hansen (2002). Fröhlich (2003) provides a literature review of models treating the effects of increased road supply.…”
Section: Introductionsupporting
confidence: 64%
“…A comprehensive study of the impacts of urban design factors on US vehicle travel found that a 10% increase in urban road density (lane-miles per square mile) increased per capita annual VMT by 0.7% [11]. In a study of eight new urban highways in Texas over several years.…”
Section: Induced Demand: An Overviewmentioning
confidence: 99%